(untitled) (Bangladesh Journal of Child Health, 2010)
Back Ground: In the past, it was believed that the undescended testis suffered no adverse changes until after puberty and surgical intervention was not necessary until 12 to 15 years of age. In the recent past, orchiopexy has been recommended in the second year of life, but now orchiopexy is recommended at 6 month of age. This is because the first sign of damage to the testes are identified at about 6 month of age. Treatment of undescended testes improves fertility and endocrine function, reduces the risk of torsion & trauma, facilitates examination of testis and creates a normalappearing scrotum. The mainstay of therapy for the palpable undescended testes is surgical orchiopexy with creation of a subdartos pouch. When the testis is nonpalpable diagnostic laparoscopy is useful for management planning Aim: The aim of this study was to ascertain the experience of management of undescended testis in this hospital. Methods: The study was conducted at Institute of Child Health & Shishu Sasthya Foundation Hospital. Case notes of 57 patients who had undergone surgical management for undescended testis between December 1999 and November 20007 were reviewed. The patients were separated into 2 groups: patients with palpable undescended testis and patients with impalpable testis. Surgical management was not done before 6 month of age. Open orchiopexy was performed in palpable group. For impalpable group, diagnostic laparoscopy was done and managed accordingly. Results: The median age at operation was 7.2 years (range 06 month to 14 years). Orchiopexy was done at the age of 6 month in 2 patients. Among 57 cases, thirty-six patients had palpable testes and twenty-one patients had impalpable testis. Twenty patients had right sided undescended testis and four had bilateral. Clinical inguinal hernia was present in 2 cases with right sided palpable undescended testis. Hypospadias was present in 1 patient with right sided palpable undescended testis. Open orchiopexy was performed in 36 patients (palpable group). Laparoscopy was done 21 patients (impalpable group). In impalpable group (21) ultra-sonogram found testis in 7 cases and was doubtful in 2 cases. On diagnostic laparoscopy only 2 vanishing testes were found. Lap assisted single stage orchiopexy was performed in 1 patients. First stage of Fowler-Stephen was done laparoscopically in 18 cases. Second stage of this procedure was done in open method in 2 patients. There was no postoperative complication. Conclusions: Orchiopexy is a safe procedure for the children even at the age of 6 months. With laparoscopy impalpable testis can be safely diagnosed and managed. DOI: 10.3329/bjch.v31i1.6069 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 16-21